THE INFLUENCE OF THE DRILL AND PRACTICE METHOD IN LEARNING ENGLISH VOCABULARY AT SMAS GKPI PADANG BULAN MEDAN - Kethrin Simamora; Harpen H.P Silitonga; Febrina S.L. Lambantobing (Program Studi Pendidikan Bahasa Inggris, 2025)
Mastering vocabulary is essential in learning English as it serves as the foundation for developing students’ language skills such as speaking, reading, and writing. However, many students still struggle to expand and retain English vocabulary due to limited practice and lack of effective learning strategies. This discrepancy between theoretical understanding and classroom practice highlights the need for more efficient teaching methods. Therefore, this study aims to examine the effect of the Drill and Practice method on students’ mastery of English vocabulary. The research employed a quantitative experimental design involving two groups of tenth-grade students at SMAS GKPI Padang Bulan Medan. Vocabulary mastery was measured through pre-tests and post-tests consisting of 25 multiple-choice items assessing students’ ability to recognize, comprehend, and apply vocabulary in context. The experimental group received treatment through structured Drill and Practice activities—including choral, individual, and spelling drills—while the control group was taught using conventional methods. The results showed a significant improvement in the experimental group’s post-test mean score (52.6 to 64.8) compared to the control group (52.2 to 58.6). Statistical analysis using an independent t-test indicated that the obtained t-value (3.558) exceeded the critical value (2.024) at the 0.05 significance level. The findings suggest that the Drill and Practice method effectively improves students’ vocabulary retention, accuracy, and fluency. It is recommended that English teachers integrate this method into vocabulary instruction to enhance students’ engagement and confidence in learning English.